Answer:
Step-by-step explanation:
All we have to do is input the given values of x into the functions.
The first function:
f(x) = x^2 - 5x - 6
f(0) = 0^2 - 5(0) - 6 = 0 - 0 - 6 = -6
f(0) = -6
f(2) = 2^2 - 5(2) - 6 = 4 - 10 - 6 = -12
f(2) = -12
f(-1) = -1^2 - 5(-1) - 6 = 1 + 6 - 6 = 1
f(-1) = 1
f(6) = 6^2 -5(6) - 6 = 36 - 30 - 6 = 0
f(6) = 0
The second function:
f(x) = x^3 - x^2 - 12
f(0) = 0^3 - 0^2 - 12 = 0 - 0 - 12 = -12
f(0) = -12
f(2) = 2^3 - 2^2 - 12 = 8 - 4 - 12 = -8
f(2) = -8
f(-1) = -1^3 - (-1)^2 - 12 = -1 - 1 - 12 = -14
f(-1) = -14
f(6) = 6^3 - 6^2 - 12 = 216 - 36 - 12 = 168
f(6) = 168
The third function:
f(x) = 5 * 2^x
f(0) = 5 * 2^0 = 5 * 1 = 5
f(0) = 5
f(2) = 5 * 2^2 = 5 * 4 = 20
f(2) = 20
f(-1) = 5 * 2^-1 = 5 * 0.5 = 2.5
f(-1) = 2.5
f(6) = 5 * 2^6 = 5 * 64 = 320
f(6) = 320
Answer:
Step-by-step explanation:
(a + b + c)³ = a³ + b³ + c³ + 3a²b + 3a²c + 3ab² + 3cb² +3 ac² + 3bc² + 6abc
a = 5a ; b =y ; c = z
(5x + y + z)(5z + y + z )(5z + y +z) = (5x + y +z)³
= (5x)³ + y³ +z³ + 3(5x)²y + 3(5x)²z + 3(5x)*y² + 3*z*y² + 3*5x*z² + 3*y*z² + 6*5x*y*z
= 125x³ + y³ +z³ + 3*25x²y + 3*25x²*z + 15xy² + 3zy² + 15xz² + 3yz² + 35xyz
= 125x³ + y³ + z³ + 75x²y + 75x²z + 15xy² + 3zy² + 15xz² + 3yz² + 35xyz
275 beacues if u and 50 five times it would of been 250 but u an the five two the 50 and u and 55 five times and u get 275
Hope i help <span>42/2= 21
21 / 3 = 7
Answer=2 x 3 x 7</span>